Implementasi Peraturan Menteri Sosial Nomor 1 Tahun 2018 Tentang Program Keluarga Harapan dalam Pemilihan Keluarga Penerima Manfaat Program Keluarga Harapan di Desa Tempatan Kecamatan Sebawi - Hamdani (AL-SULTHANIYAH, 2024)
The problem of this study stems from the fact that families who are classified as well-off are still registered as PKH beneficiaries. On the other hand, there are families who are economically disadvantaged but are not registered. The focus of the problem in this study is how is the implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program in determining beneficiary families in Tempatan Village and what are the inhibiting factors? This type of research is qualitative research which is field research with an empirical juridical approach. To obtain data, researchers used observation, interview and documentation techniques. Based on the research results, it can be concluded that: The Family Hope Program (PKH) cannot be said to be evenly distributed. It is still found that residents of well-off families (rich) are included in the PKH beneficiary category and there are still underprivileged residents (poor) who are not registered as Beneficiary Families. The inhibiting factors in the implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program are that the data used is not updated, the limited role of the local village government in determining the list of PKH recipients, planning in the Family Hope Program in Tempatan Village, Sebawi District has not been mature in creating independence or reducing poverty.